VALIDITAS KONSTRUK INSTRUMEN KETERAMPILAN ABAD 21 PADA PEMBELAJARAN IPAS BERBASIS PROBLEM BASED LEARNING BERBANTUAN AUDIOVISUAL - Hendrik Setiawan; Amaliah Nafiati, Dewi; Munadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to validate the construct of a 21st century skills assessment instrument used in IPAS learning with Problem Based Learning (PBL) and audiovisual media. The instrument measures four dimensions: Critical Thinking, Creativity, Communication, and Collaboration (4C). Using a quantitative non-experimental design, the study involved 121 sixth-grade students from five elementary schools in Brebes District, selected through purposive sampling. Validation included item validity testing using Pearson Product Moment correlation (r > 0.361) and construct validity through Confirmatory Factor Analysis (CFA). Results showed all items were valid (r = 0.578-0.875), with high factor loadings (0.816-0.892), strong Construct Reliability (CR = 0.841-0.891), and adequate Average Variance Extracted (AVE = 0.569-0.672). Model fit indices (CFI = 0.982; TLI = 0.979; RMSEA = 0.034) confirmed excellent fit. The 4C instrument demonstrates strong validity, making it suitable for assessing 21st century skills in PBL-based IPAS learning with audiovisual media.